Dengue fever in renal allograft recipients: Clinical course and outcome. Issue 3 (30th March 2018) - Subbiah, Arunkumar; Bagchi, Soumita; Bhowmik, Dipankar; Mahajan, Sandeep; Yadav, Raj K.; Chhabra, Yogesh; Agarwal, Sanjay
Abstract: Background: There are annual outbreaks of dengue infection in tropical and subtropical countries. This retrospective study aimed to assess the clinical manifestation of dengue and outcome in renal transplant recipients. Methods: Renal transplant recipients diagnosed with dengue in the nephrology department during the outbreak from August 2015 to December 2015 were included in the study. Results: Twenty patients developed dengue presenting during the outbreak. Mean age was 31.9 ± 8.8 years and all were males. Two patients had severe dengue (dengue hemorrhagic fever, dengue shock syndrome). Clinical presentation included febrile illness (95%), myalgia (65%), headache (30%), retro‐orbital pain (10%), and mucocutaneous bleeding manifestations (10%). Three (15%) had third space fluid accumulation and 2 (10%) had hypotension. Ninety percent patients had thrombocytopenia, with 4 requiring platelet transfusion. Leucopenia (WBC < 4000/mm 3 ) developed in 50% patients. About 60% had transient transaminitis. One patient with severed dengue expired and 1 recovered with IV immunoglobulin therapy. About 40% patients had rise in serum creatinine, with complete recovery in all patients. Conclusion: Clinical manifestations of dengue infection in renal transplant recipients were similar to that in general population. However, leucopenia necessitating temporary withdrawal of immunosuppression was common. Renal dysfunction was frequent but completely reversible.